20 år med fysikkprestasjoner i fritt fall Analyser fra TIMSS Advanced og andre internasjonale studier - Hole, Arne (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2019)
"The book discusses various challenges and solutions related to the coordination of health and welfare services. Coordination is central to creating integrated services for users with complex needs. In order to understand the challenges and opportunities associated with creating such services, one needs knowledge related to organizations and the organizational context. The book's chapters takes on an organizational perspective where patterns and explanations are sought in formal and informal structures, processes and culture. The users' need for services often cross established boundaries, both organizational and professional. The authors highlight the possibilities and limitations of some selected solutions that will help to cut across or break down such boundaries. Examples of such solutions are user involvement, interdisciplinary collaboration, team organizations, coordinators, standardization and patient pathways, digitization and decision-making tools for employees who work in the services. One chapter summarizes three different theoretical research approaches for analyzing coordination and collaboration. The target group is researchers, university and college employees and students of the health and welfare sector. The book also will be of interest for user organizations as well as administrative and professional decision-makers in public and private businesses."